"Free"-to-play game: Governing the everyday life of digital popular culture. (September 2022) - Lassila, Erkki M.
Abstract: This research aims to uncover the transformative powers inherent and hidden in big data technologies, looking for revealing new areas for governing. By tracking information on the conduct of everyday users of digital apps, these technologies allow the game developers, in their pursuit of their own economic goals, to exploit the users. Employing empirical examples from the free-to-play gaming industry, this research demonstrates how the notion of governmentality gets a new, broader meaning in the modern digital space, where big data technologies are used for control and governing, by adding new insights to the existing knowledge on such digital spaces. The ability to analyze very effectively users' behavioral data with the help of modern big data technologies has changed, not only the gaming industry, but also how playing games is expected to happen in our modern digital world. The calculative practices of the accounting function, generating associations between separate and distant domains, and translating complex processes into a financially comprehensible form, have been involved in transforming application consumption. From a simple mode of occasional entertainment for individuals, gaming has become a daily attention craving, constantly changing, privacy trespassing, and data generating labor process.